The Influence of COVID-19 on Community Participation in the Mayoral Election: A Case Study from Barombong Village, Makassar City - Putra, Wahyu Adi; Hakim, Lukman; Hawing, Hardianto (Journal of Government and Political Issues, 2023)
This study aimed to assess the impact of COVID-19 on public participation in the mayoral election, focusing on the Barombong sub-district of Makassar City. Employing a quantitative approach and field research methodology, data was collected by distributing 98 questionnaires to residents of Barombong sub-district, Tamalate sub-district, who participated in the 2020 Makassar City Mayoral Election. The data analysis methods included descriptive analysis, classical assumption tests, simple linear regression analysis, and hypothesis testing using SPSS 21. The findings revealed that COVID-19 (X) had a positive influence on Community Participation (Y) in the Makassar Mayoral Election. Consequently, the primary hypothesis of this study was confirmed, indicating that COVID-19 did influence community participation in the election. While the general perception of COVID-19 is concerning, this research suggests that its impact on voter turnout was minimal, with only a 0.3 percent increase in community participation in the mayoral election.